Valores inteiros de funções geradoras de sequências recorrentes: os resultados de Fibonacci e Lucas - Ribeiro, Wendell Fernandes (2019)
This paper aims to present some combinatorial and recurrence problems that can be solved using the Generator Functions; also show an interpretation for the Fibonacci Sequence and the Lucas Succession using these concepts, as well as the conditions for these functions to result in an integer. Finally, it should be noted that this study may contribute to future research in both Basic and Higher Education.